Interpreting U–Pb data from primary and secondary features in lunar zircon - Grange, Marion; Pidgeon, Robert; Nemchin, Alexander; Timms, Nicholas Eric; Meyer, C. (Pergamon-Elsevier Science Ltd, 2013)
In this paper, we describe primary and secondary microstructures and textural characteristics found in lunar zircon and discuss the relationships between these features and the zircon U–Pb isotopic systems and the significance of these features for understanding lunar processes. Lunar zircons can be classified according to: (i) textural relationships between zircon and surrounding minerals in the host breccias, (ii) the internal microstructures of the zircon grains as identified by optical microscopy, cathodoluminescence (CL) imaging and electron backscattered diffraction (EBSD) mapping and (iii) results of in situ ion microprobe analyses of the Th–U–Pb isotopic systems. Primary zircon can occur as part of a cogenetic mineral assemblage (lithic clast) or as an individual mineral clast and is unzoned, or has sector and/or oscillatory zoning. The age of primary zircon is obtained when multiple ion microprobe analyses across the polished surface of the grain give reproducible and essentially concordant data. A secondary set of microstructures, superimposed on primary zircon, include localised recrystallised domains, localised amorphous domains, crystal–plastic deformation, planar deformation features and fractures, and are associated with impact processes. The first two secondary microstructures often yield internally consistent and close to concordant U–Pb ages that we interpret as dating impact events. Others secondary microstructures such as planar deformation features, crystal–plastic deformation and micro-fractures can provide channels for Pb diffusion and result in partial resetting of the U–Pb isotopic systems.